In situ cross–linked chitosan hydrogels via Michael addition reaction based on water–soluble thiol–maleimide precursors. (October 2019) - Guaresti, Olatz; Basasoro, Senda; González, Kizkitza; Eceiza, Arantxa; Gabilondo, Nagore
Graphical abstract: Highlights: Successful functionalization of CsSH, resulting in a water–soluble derivative. Effective strategy for the cross–linking of hydrogels between CsSH and synthesized BMI. Fast gelation times, resulting in high storage modulus values and significant structural parameters. The excellent properties of the hydrogels were found to be significant for biomedicine. Abstract: Thiol modified chitosan (CsSH) was covalently cross–linked with a water–soluble bismaleimide (BMI) to obtain chitosan–based hydrogels by thiol–Michael addition reaction at physiological conditions. By modifying the composition of the as–prepared hydrogels, final properties could be modulated. Thus, the rheological and swelling behaviour were controlled by altering the amount of cross–linking agent in the networks. An increase in the cross–linker ratio leaded to an increase in the hydrogel storage modulus and decrease in swelling ratio due to provided rigidity to the structure and a higher cross–linked degree. Furthermore, 3D porous structures were observed to be sensitive to pH stimulus and showed interesting degradation kinetics under specific enzymes, suggesting the formation of these novel materials to be worthy of biomedical applications.